2016
DOI: 10.5194/cp-12-543-2016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low ancient greenhouse climate temperature gradients on the ocean's overturning circulation

Abstract: Abstract. We examine whether the reduced meridional temperature gradients of past greenhouse climates might have reduced oceanic overturning, leading to a more quiescent subsurface ocean. A substantial reduction of the pole-toEquator temperature difference is achieved in a coupled climate model via an altered radiative balance in the atmosphere. Contrary to expectations, we find that the meridional overturning circulation and deep ocean kinetic energy remain relatively unaffected. Reducing the wind strength al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Both the deepening of the Rio Grande Rise and enhanced mixing associated with global warming would have increased the capacity of the overturning circulation in the Atlantic Ocean to transport heat. These interpretations of our new Nd-isotope data are consistent with observed changes in Late Cretaceous to early Paleogene Nd-isotope records from the Pacific Ocean 42 and Earth system modelling results, which indicate that vigorous ocean circulation and strong vertical mixing resulted in increased oceanic heat transport and reduced equator–pole temperature gradients 42 , 43 . Higher oceanic heat transport efficiency likely also set the stage for the occurrence of brief hyperthermals which were frequently superimposed on the overall temperature rise of the Eocene hothouse 41 .…”
Section: Discussionsupporting
confidence: 88%
“…Both the deepening of the Rio Grande Rise and enhanced mixing associated with global warming would have increased the capacity of the overturning circulation in the Atlantic Ocean to transport heat. These interpretations of our new Nd-isotope data are consistent with observed changes in Late Cretaceous to early Paleogene Nd-isotope records from the Pacific Ocean 42 and Earth system modelling results, which indicate that vigorous ocean circulation and strong vertical mixing resulted in increased oceanic heat transport and reduced equator–pole temperature gradients 42 , 43 . Higher oceanic heat transport efficiency likely also set the stage for the occurrence of brief hyperthermals which were frequently superimposed on the overall temperature rise of the Eocene hothouse 41 .…”
Section: Discussionsupporting
confidence: 88%
“…However, modeling studies suggest that Cretaceous to Eocene deep water formation and downwelling may have occurred due to density contrasts created by seasonal changes in surface water temperatures and salinity (with or without the presence of sea ice) [e.g., Lunt et al , ; Huber and Sloan , ; Otto‐Bliesner et al , ]. More recently, Sijp and England [] demonstrated that reduced pole‐to‐equator sea surface temperature gradients, such as those reconstructed from the Tasman Gateway region during the early Eocene [e.g., Bijl et al , ], had little effect on modeled ocean circulation patterns or deep water formation in the southern high latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Although deep oceans cooled during the Eocene [e.g., Zachos et al , ], much less is known about the associated changes in circulation patterns and dominant source regions of deep water formation. Modeling and geochemical data‐based studies have proposed both the Southern Ocean and the low latitudes as regions of deep water formation during the warmest periods of the Cretaceous and early Cenozoic [e.g., Brass et al , ; Kennett and Stott , ; Bice et al , ; Cramer et al , ; Hague et al , ; Pak and Miller , ; Scher and Martin , ; Sijp and England , ; Thomas , ; Thomas et al , ], leaving large uncertainty about the link between ocean circulation and climate during the early Cenozoic greenhouse (e.g., the early Eocene “equable climate paradox”) [ Huber and Caballero , ]. This is in part due to a lack of detailed records documenting Eocene climate and ocean circulation in key geographical areas.…”
Section: Introductionmentioning
confidence: 99%